Sistem Penjaminan Mutu pada Perguruan Tinggi Keagamaan Islam Negeri di Sulawesi Selatan - Musgamy, Awaliah; Arsyad, Azhar; Siraj, Arifuddin; Wayong, Muh (Jurnal Diskursus Islam, 2016)
The quality assurance system at the State Islamic Higher Education in South Sulawesi is already running by using a variety of credible quality documents through a determination. These various quality documents are then carried out as a normative-academic reference in the quality assurance system for further evaluation. The evaluation results are then controlled by trying to find alternative solutions to various arising problems that are accompanied by efforts to improve the quality itself. The constraint of the quality assurance system is the maximum dissemination of various quality documents so that it triggers a refresive attitude among some of the academic community and their lack of attention to the applied quality assurance system. Another constraint faced is that the Islamic education paradigm has not been maximally accommodated in various quality policies with all its derivatives as well as the incomplete fulfillment of each standard. These various constraints tend to emerge beginning with the determination to then have implications for other Islamic education quality assurance cycles which in this case are the implementation, evaluation, control and improvement. Even on a macro scale, the Islamic education quality assurance system still dwells on the establishment, implementation, and evaluation and is still not maximal on control and improvement because there is an impression that quality assurance is carried out for pragmatic purposes, especially accreditation. The efforts made by the State Islamic Higher Education in South Sulawesi in overcoming various constraints to the quality assurance system are maximizing the socialization of the quality assurance system that is applied in each cycle starting from the establishment, implementation, evaluation, control and improvement. In addition, there is a need to adjust the quality assurance system policy with all its derivatives with the paradigm developed by the institution which is then accompanied by maximum fulfillment of each standard.